Evaluation of [18F]2FP3 in pigs and non‐human primates. (6th December 2018) - Hansen, Hanne D.; Constantinescu, Cristian C.; Barret, Olivier; Herth, Matthias M.; Magnussen, Janus H.; Lehel, Szabolcs; Dyssegaard, Agnete; Colomb, Julie; Billard, Thierry; Zimmer, Luc; Tamagnan, Gilles; Knudsen, Gitte M.
Abstract : So far, no suitable 5‐HT7 R radioligand exists for clinical positron emission tomography (PET) imaging. [ 18 F]2FP3 was first tested in vivo in cats, and the results were promising for further evaluations. Here, we evaluate the radioligand in pigs and non‐human primates (NHPs). Furthermore, we investigate species differences in 5‐HT7 R binding with [ 3 H]SB‐269970 autoradiography in post‐mortem pig, NHP, and human brain tissue. Specific binding of [ 18 F]2FP3 was investigated by intravenous administration of the 5‐HT7 R specific antagonist SB‐269970. [ 3 H]SB‐269970 autoradiography was performed as previously described. [ 18 F]2FP3 was synthesized in an overall yield of 35% to 45%. High brain uptake of the tracer was found in both pigs and NHPs; however, pretreatment with SB‐269970 only resulted in decreased binding of 20% in the thalamus, a 5‐HT7 R–rich region. Autoradiography on post‐mortem pig, NHP, and human tissues revealed that specific binding of [ 3 H]SB‐269970 was comparable in the thalamus of pig and NHP. Despite the high uptake of [ 18 F]2FP3 in both species, the binding could only be blocked to a limited degree with the 5‐HT7 R antagonists. We speculate that the affinity of the radioligand is too low for imaging the 5‐HT7 Rs in vivo and that part of the PET signal arises from targets other than the 5‐HT7 R. Abstract : Here, we evaluated [ 18 F]2FP3 as a PET radioligand for the cerebral 5‐HT7 receptor in pigs and non‐human primates. We found high uptake of [ 18 F]2FP3 in both species; however, the binding could only be blocked to a limited degree with the 5‐HT7 receptor antagonist SB‐269970. We speculate that the affinity of the radioligand is too low for imaging the 5‐HT7 receptors in vivo. Lastly, we also investigated the specific binding of [ 3 H]SB‐269970 in post‐mortem pig, non‐human primate, and human brain tissue.